Clinical Findings in Dogs Trained for Awake-MRI - Berns, Gregory S.; Spivak, Mark; Nemanic, Sarah; Northrup, Nicole (Frontiers in Veterinary Science, 2018)
Training dogs for awake-MRI began in 2012 for the study of canine cognition. Although originally envisioned as a research technique to understand the neural mechanisms of canine cognitive function, its potential as a new diagnostic clinical tool has become apparent. A high-quality structural scan of the brain can be acquired without sedation or anesthesia in as little as 30 s in a well-trained dog. This has opened the possibility of longitudinal imaging of CNS disease with MRI both as a means of monitoring treatment and potentially as a surveillance tool for inflammatory and neoplastic brain diseases in high-risk breeds. This same training can be used to image other body regions, such as the abdomen, enabling clinicians to screen for abdominal disease using cross sectional imaging without the need for anesthesia and without exposing the patient to ionizing radiation. We present four examples of dogs trained for awake-MRI who developed: 1) nasal carcinoma; 2) brain tumor; 3) abdominal lipoma; 4) idiopathic epilepsy.